The Budding Rose: Relationships among Henry James's Characters and the effects of these Relationships on Character Development - McKenzie, Maureen W. (My University, 1982)
This thesis explores the complexity of human relationships in Henry James's novels: The Portrait of a Lady, The Bostonians, and The Golden Bowl. Special attention is paid to the influences which James's characters have upon each other. Olive and Ransom's influence on Verena in The Bostonians, Osmond and Madame Merle's influence on Isabel in The Portrait of a Lady, and Amerigo and Charlotte's influence on Maggie in The Golden Bowl, are examined. Both the positive and the negative results of Olive's, Ransom's, Osmond's, Madame Merle's, Amerigo's, and Charlotte's desires are discussed in view of Verena's, Isabel's, and Maggie's growing awareness of themselves and the world around them. Verena, Isabel, and Maggie follow a linear progression from innocence to awareness and the correlation between this progression and the intensity of love is also studied.
Keywords: English; English Language and Literature; English Language and Literature